Effect of typhoon‐induced intertidal‐flat erosion on dominant macrobenthic species (Meretrix meretrix). Issue 12 (24th October 2021) - Shi, Benwei; Yang, Shi Lun; Temmerman, Stijn; Bouma, Tjeerd; Ysebaert, Tom; Wang, Sikai; Zhang, Yingxin; Wu, Jihua; Yang, Haifei; Zhang, Longhui; Zuo, Liqin; Wang, Ya Ping
Abstract: Benthic animal populations inhabiting intertidal flats provide important ecosystem functions and services that may be disrupted by physical disturbances such as tropical cyclones, which are predicted to increase in frequency and intensity under future climate change. However, the spatial reach at which tropical cyclones impact macrobenthos populations in intertidal flats remains poorly understood. We examined whether a typhoon with a center that remained more than 1400 km away from the study site could trigger severe erosion of intertidal flats and adversely affect macrobenthos populations. We undertook simultaneous measurements of hydrodynamics (waves, currents), morphodynamics (erosion, accretion) and density and biomass of the macrobenthic bivalve Meretrix meretrix during the passage of this typhoon, on an intertidal flat on the Chinese coast. Our results showed that, in spite of the considerable distance from the storm center, the bed shear stress greatly exceeded the critical value for erosion, resulting in rapid erosion of approximately 10 cm and a nearly 50% reduction in both the density and the biomass of the clam species. Our findings suggest that if storms become more frequent and more intense in a future warmer climate, they may increase physical disturbances to intertidal flats and their benthic animal populations, even at great distances from storm centers.